The traveling waqf: Property, religion, and mobility beyond China - Erie, M (Brill, 2018)
For most of their millennial history in China, Muslims have established pious endowments called waqfsthat served a variety of functions, including providing land to build mosques. The founding of waqfsradically changed in 1949, when the Communists confiscated land. Recently, a Hui who was performing the hajj in Saudi Arabia discovered a pre-Communist waqfiyya or document that established a waqf in Gansu Province in northwest China. The contemporary Chinese property regime prohibits religious land and hence the waqfiyya is legally void, yet its return afforded the Hui an opportunity to reflect on the relationships between law, lineage, and public goods, laying a foundation for an historical anthropology of Chinese waqfs. Drawing on material from historical Gansu and ethnographic encounters, I argue that whereas shariʿa suffered a kind of “structural death” in China, it does have its own “afterlife,” as illustrated in documents that travel across time and assume new meanings through transnational mobility and memory.